Inisiasi Kurikulum Stimulasi, Deteksi dan Intervensi Dini Tumbuh Kembang (SDIDTK) Bagi Guru PAUD Kecamatan Kesamben Kabupaten Jombang - Prihartanti, Niken Grah; Mulyaningsih, Erika Agung (Jurnal Abdimas Jatibara, 2023)
The period of life that is very important in children is the first five years of life which are very important. At this age children can grow and develop according to age if they get optimal stimulation. Stimulation of Detection and Early Intervention of Growth and Development (SDIDTK) in children is an effort to stimulate the basic abilities of children aged 0-6 years so that they grow and develop optimally. PAUD teacher is a profession that has an important role in detecting growth and development in children. Through training activities on SDIDTK deviations in the growth and development of PAUD children can be detected early. The targets of this training were PAUD teachers in the Kesamben sub-district, totaling 64 people. This activity is in collaboration with partners, namely the Amil Zakat Ummul Quro Institute (LAZ-UQ) in Jombang Regency and the Raudhatul Atfal Teachers' Association (IGRA) in Kesamben District. The Methods this community service is carried out using the lecture method and direct practice by assessing growth and development in early childhood. This activity ran optimally marked by the enthusiasm of PAUD teachers in discussion sessions and demonstrations of growth and development assessment. Results is overall, the participants had never received the stimulation detection curriculum material for child growth and development before, so the participants considered that this activity really needed to be refreshed periodically. Stimulation activities for Early Detection and Intervention on Growth and Development can continue to be carried out to determine the growth and development of children. The conclusions there is a possibility that the child's growth and development is not according to his age, then the next steps can be determined. Children who receive targeted and regular stimulation will develop faster than children who receive less stimulation.